13 A two-period, open-label trial evaluating the efficacy and safety of dasiglucagon for the treatment of children with hyperinsulinaemic hypoglycaemia. (22nd November 2019) - Morgan, Kate; Taylor, Nina; Carroll, Natasha; Shah, Pratik
Abstract : Hyperinsulinaemic Hypoglycaemia (HH) is characterised by the inappropriate secretion of insulin from the pancreatic βcells in relation to blood glucose concentration. HH is the most common cause of severe and persistent hypoglycaemia in infancy. Approximately 50% of children with HH experience neurodevelopmental abnormalities caused by severe hypoglycaemia. Prompt recognition and successful management is paramount to ensure hypoglycaemic brain injury and neurological sequelae are avoided. Currently, the only approved treatment for HH is diazoxide, but it has unpleasant side effects- pulmonary hypertension, fluid retention, hypertrichosis and coarse facial features. The management of diazoxide-unresponsive HH is a real therapeutic challenge. Current off-label therapies include intravenous/subcutaneous glucagon, subcutaneous octreotide and long-acting somatostatin, however, they are often insufficient, and a 98% pancreatectomy or continuous feeds may be required. Glucagon is an effective treatment of HH, and has been shown to be effective in the establishment of HH diagnosis and initiation of medical therapy. Whilst administration of glucagon to patients with HH is used short-term in the hospital setting, long-term glucagon treatment is complicated. Current glucagon products are unstable and form fibrils within hours after reconstitution. This fibril formation may lead to infusion set clotting, catheter obstruction, and dosing errors, that may cause acute severe hypoglycaemia. Therefore, in a home-care setting, this fibril formation and associated risk of dosing errors carry the risk of hypoglycaemic events, which is a major barrier for using currently marketed glucagon products for long-term treatment of patients with HH For the first time in over 40 years, new drugs are being developed for treatment in HH. Dasiglucagon is a stable analog of glucagon that has been specifically designed to overcome the issues with fibril formation and instability in solution observed with marketed glucagon products. This year, GOSH dosed the first patient in the world in this global trial.